1988
DOI: 10.1111/j.1476-5381.1988.tb11604.x
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the stimulative effect of thapsigargin, a non‐TPA‐type tumour promoter, on arachidonic acid metabolism in rat peritoneal macrophages

Abstract: 1 At concentrations above IO ngml 1, the tumour promoter thapsigargin stimulates the release of radioactivity from [3H]-arachidonic acid-labelled macrophages harvested from rat peritoneal cavity. 2 The release of radioactivity from prelabelled macrophages was augmented more than additively when the cells were incubated in the medium containing both thapsigargin (10 ng ml-) and other tumour promoters (lOngml-1), such as 12-0-tetradecanoylphorbol-13-acetate (TPA), teleocidin and aplysiatoxin. 3 Thapsigargin requ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
17
0

Year Published

1989
1989
2015
2015

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(18 citation statements)
references
References 19 publications
(20 reference statements)
1
17
0
Order By: Relevance
“…A solution of soluble starch (Wako Pure Chemicals, Osaka, Japan) and Bactopeptone (Difco, Detroit, MI, USA), 5% each, was injected intraperitoneally into male Sprague-Dawley rats (30 -350 g, specific pathogen-free, Charles River Japan, Kanagawa, Japan) at a dose of 5 mL/100 g body weight. Four days later, the rats were killed by cutting the carotid artery under diethylether anesthesia and the peritoneal cells were harvested (Ohuchi et al, 1988). The animal experiment was performed according to the procedure approved by the Animal Ethics Committee of the Graduate School of Pharmaceutical Sciences, Tohoku University, Sendai, Japan.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A solution of soluble starch (Wako Pure Chemicals, Osaka, Japan) and Bactopeptone (Difco, Detroit, MI, USA), 5% each, was injected intraperitoneally into male Sprague-Dawley rats (30 -350 g, specific pathogen-free, Charles River Japan, Kanagawa, Japan) at a dose of 5 mL/100 g body weight. Four days later, the rats were killed by cutting the carotid artery under diethylether anesthesia and the peritoneal cells were harvested (Ohuchi et al, 1988). The animal experiment was performed according to the procedure approved by the Animal Ethics Committee of the Graduate School of Pharmaceutical Sciences, Tohoku University, Sendai, Japan.…”
Section: Methodsmentioning
confidence: 99%
“…Rat peritoneal macrophages were harvested from male Sprague-Dawley strain rats according to the procedure described previously (Ohuchi et al, 1988). Macrophages were seeded at a density of 7.5 × 10 5 cells/0.5 mL/well in 24-well plastic tissue culture dishes (Corning Glass Works, Corning, NY, USA) or 3 × 10 6 cells/2 mL/well in 6-well plastic tissue culture dishes (Corning Glass Works) in Eagle's minimal essential medium (EMEM, Nissui, Tokyo, Japan) containing 10% calf serum (Flow Laboratories, and the aqueous layer was again partitioned successively with chloroform (26 g), ethyl acetate (15 g) and n-butanol (24 g).…”
Section: Isoquercitrinmentioning
confidence: 99%
“…not activate protein kinase C (3,4) or inhibit protein phosphatases. Thapsigargin induces acute responses in a large variety of cell types (4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14), but thapsigargin-induced cellular activation appears, in all cases, to be initiated by a single common event: a rapid and pronounced increase in the concentration of cytosolic free Ca2l ([Ca2+]1) that occurs via a direct discharge of intracellular stored Ca2l without hydrolysis of inositolphospholipids (4,8,12). These results imply that thapsigargin might act directly on a recognition site associated with the intracellular Ca2+ store (7,15).…”
mentioning
confidence: 99%
“…After cholinergic stimulation, however, oscillations were observed only at doses of carbachol below the EC50 for that agonist . In addition to differences in calcium signaling patterns, it was observed that although the majority of cells in which histamine-stimulated secretion was detected also responded with increased [Ca2+] Recently, an unusual tumor promoter, thapsigargin, a sesquiterpene lactone occurring naturally in the roots of Thapsia garganica L. (Christensen et al, 1982), has been shown to elevate [Ca2+], in several different cell types (Thastrup et al, 1987;Ohuchi et al, 1988;Scharff et al, 1988;Brayden et al, 1989;Cheek and Thastrup, 1989;Foder et al, 1989;Takemura et al, 1990;Thastrup et al, 1990). Unlike 1 2-0-tetradecanoyl phorbol-1 3-acetate (TPA), thapsigargin has not been found to increase InsP3 or to activate protein kinase C (Hakii et al, 1986;Jackson et al, 1988).…”
Section: Introductionmentioning
confidence: 99%